2012
DOI: 10.1017/thg.2012.58
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Whole Genome Linkage of Pulse Pressure in Chinese Twin Pairs

Abstract: Elevated pulse pressure is associated with cardiovascular disorders and mortality in various populations. The genetic influence on pulse pressure has been confirmed by heritability estimates using related individuals. Recently, efforts have been made in mapping genes that are linked to the phenotype. We report results on our heritability and linkage study conducted on the Chinese population in mainland China where cardiovascular and cerebrovascular diseases are becoming the leading cause of death. A total of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…Further studies will be required to clarify functional relation between FLJ12164 and TGFA responsible for blood pressure regulation. Interestingly, a recent linkage study investigating heritability of PP among Chinese twin pairs found3 linkage peaks on chromosomes 11, 12 and 18 [33] , which are different from ours. However, instead of ambulatory BP monitoring, that study was based on a single-point BP value.…”
Section: Discussioncontrasting
confidence: 99%
“…Further studies will be required to clarify functional relation between FLJ12164 and TGFA responsible for blood pressure regulation. Interestingly, a recent linkage study investigating heritability of PP among Chinese twin pairs found3 linkage peaks on chromosomes 11, 12 and 18 [33] , which are different from ours. However, instead of ambulatory BP monitoring, that study was based on a single-point BP value.…”
Section: Discussioncontrasting
confidence: 99%
“…An English twin study certified similar heritability of PP compared to our findings (43%) [25]. A Chinese twin study provided both epidemiological and molecular genetic evidence for the genetic dissection of pulse pressure, which could help in fine mapping and in characterizing genes that are involved in the regulation of PP [26]. A recent Chinese twin study assessed eight metabolic factors (body mass index, waist circumference, waist-to-hip ratio, total serum cholesterol, serum triglycerides, serum uric acid besides systolic and diastolic blood pressure) in 508 twin pairs aged 8-17 years and reported that the effect of genetic factors on most metabolic traits decreased from childhood to adolescence [27].…”
Section: Cardiovascular Risk Factorssupporting
confidence: 81%
“…A total of 23 heritability estimates in SBP, 22 estimates in DBP, 7 in HR and 4 in PP were identified from 17 twin studies since year 2001 (Baird et al, 2001; Dalageorgou et al, 2008; De Geus et al, 2007; Evans et al, 2003; Fagard et al, 2003; Jermendy et al, 2011; Jiang et al, 2012; Kennedy et al, 2005; Li et al, 2013; Mutikainen et al, 2009; Peeters et al, 2008; Snieder et al, 2003; Tarnoki et al, 2012; Vinck et al, 2001; Wu et al, 2011; Zeegers et al, 2004; Zhang et al, 2009). There were four estimates in SBP, four in DBP, and two in HR reported by sex specifically; five estimates in SBP, five in DBP, and two estimates in HR reported by age subgroup separately.…”
Section: Resultsmentioning
confidence: 99%